2014
DOI: 10.1007/s12666-014-0462-z
|View full text |Cite
|
Sign up to set email alerts
|

Damping Behavior of Metal Matrix Composites

Abstract: In the present day scenario, materials with high damping capacity and good mechanical properties are significant to suppress mechanical vibrations. In pure metals or alloys, even though the mechanical properties are fairly good, the damping capacity was found to be stumpy. Composites are a better choice which simultaneously exhibits good mechanical properties and high damping values. In the present review, the damping behavior of metals, alloys and its composites is summarized and presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…The surface modification of natural organic fibers is needed to enhance the compatibility and it has been inferred that the interfacial bonding is increased b according to the results of the viscoelastic behavior of the composites [4][5][6]. To investigate the viscoelastic behavior and structural properties of polymeric and metal matrix composite materials with the aim of determination their relevant damping and stiffness characteristics in our regular applications, dynamic mechanical analysis (DMA) was employed [7][8][9][10]. These dynamic properties obtained over a range of temperatures and frequencies are noteworthy, studies showed that the stacking sequence and fiber orientation influences the dynamic mechanical characteristics of hybrid polymeric composites [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…The surface modification of natural organic fibers is needed to enhance the compatibility and it has been inferred that the interfacial bonding is increased b according to the results of the viscoelastic behavior of the composites [4][5][6]. To investigate the viscoelastic behavior and structural properties of polymeric and metal matrix composite materials with the aim of determination their relevant damping and stiffness characteristics in our regular applications, dynamic mechanical analysis (DMA) was employed [7][8][9][10]. These dynamic properties obtained over a range of temperatures and frequencies are noteworthy, studies showed that the stacking sequence and fiber orientation influences the dynamic mechanical characteristics of hybrid polymeric composites [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…This is due to its low loss modulus (energy dissipation capacity) relative to its storage modulus (energy storage capacity). The general rise in damping capacity as temperature increases may be attributed to enhanced particle mobility and interface/ boundary sliding [17,42]. This mechanism appears somewhat inhibited for the Al-Zn reinforced with 8 wt.% Cu.…”
Section: Damping Behaviourmentioning
confidence: 99%
“…Metallic materials are generally known to possess relatively low damping capacity than ceramics so their selection will naturally arouse concern on how they influence damping capacity of the AMCs. Although works have shown that the damping capacity of AMCs reinforced by metallic particles fall within the same range as that of ceramic reinforced AMCs [16,17], the studies are limited in number for generalizations to be made. Moreover, the damping properties are known to be material system sensitive [18].…”
Section: Introductionmentioning
confidence: 99%
“…Lu et al [7] performed DMA on BFRP surfaces. DMA was used in the form to examine the viscoelastic nature and structural properties of polymer-metal matrix composites in order to evaluate their respective damping and rigidity characteristics [8][9][10][11]. Research demonstrates that the piling pattern and fiber orientation influence the complex mechanical properties of the composite hybrid polymer.…”
Section: Introductionmentioning
confidence: 99%